2017
DOI: 10.15376/biores.12.3.6665-6678
|View full text |Cite
|
Sign up to set email alerts
|

Thermal, Flammability, and Morphological Properties of Nano-composite from Fir Wood Flour and Polypropylene

Abstract: The thermal, flammability, and morphological properties were investigated for a nano-composite made from fir wood flour and polypropylene. Polypropylene (PP), fir wood flour, maleic anhydride polypropylene (MAPP), and nanosilica at 5 different concentrations (0, 2, 4, 6, and 8 phc), were mixed using an extruder, and samples were made using a handpress. Then, the hardness and the thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), limited oxygen index (LOI), X-ray diffraction (XRD), and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…The SEM images showed that compatibility and the connection between the cellulose material and polymer matrix increased by increasing of nanosilica levels. Therefore, better and stronger joints were created between the matrix and the fibers; this issue can be confirmed by considering the amount of empty spaces and homogeneity of breakage surfaces on the composites (Bazyar and Samariha 2017). In addition, an increased LOI in these samples could also confirm this issue.…”
Section: Sem Morphologymentioning
confidence: 63%
“…The SEM images showed that compatibility and the connection between the cellulose material and polymer matrix increased by increasing of nanosilica levels. Therefore, better and stronger joints were created between the matrix and the fibers; this issue can be confirmed by considering the amount of empty spaces and homogeneity of breakage surfaces on the composites (Bazyar and Samariha 2017). In addition, an increased LOI in these samples could also confirm this issue.…”
Section: Sem Morphologymentioning
confidence: 63%
“…Moreover, associate increasing of thermal stability could also be the result of associate increasing of interaction between the R-LLDPE matrix, PR fibers, and nanoparticles. 38…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, associate increasing of thermal stability could also be the result of associate increasing of interaction between the R-LLDPE matrix, PR fibers, and nanoparticles. 38 DSC measurements were performed to characterize the thermal behavior of the R-LLDPE and the R-LLDPE/PR fiber composites. The melting temperature (T m ) and melting enthalpy (H m ) of the composites samples were determined from the first heating DSC curves and are listed in Table 3.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…In addition, an enhancement of nanosilica particles could occupy part of the voids and reduce pores. Therefore, the accessibility of oxygen for ignition would be more difficult (Bazyar and Samariha 2017).…”
Section: Flammability Behaviormentioning
confidence: 99%
“…The presence of nanosilica prevented movement of the volatile and flammable gases from pores and exiting from the inner side of composites toward their surface. Therefore, the presence of nanosilica increased the LOI (Bazyar and Samariha 2017). Nanosilica filled the gaps and acted as an obstacle against penetration and movement of oxygen toward nanocomposites' structure.…”
Section: Sem Analysismentioning
confidence: 99%